Application of the Rules on the Exemption from Criminal Liability with the Imposition of a Court Fine: Problems, Features and Experience - Rostokinsky, Alexander Vladimirovich; Danelyan, Rita Surenovna; Danelyan, Sergei Vladimirovich; Tolpekin, Konstantin Andreevich; Savinkova, Elena Nikolaevna (Cuestiones Políticas, 2020)
This article examines the legal framework and practical aspects of using the criminal liability exemption with the imposition of a judicial fine. The development of Russian criminal and penal legislation, considering the humanization of the State’s criminal policy, leads to the emergence of new mechanisms for the humanization of criminal punishment and criminal responsibility itself. Many of them are of great scientific interest, such as the exemption from criminal liability with the imposition of a judicial fine. The authors examine the legal framework, the procedural order to apply this mechanism, the problems that arise in the courts that apply it in practice, the opinions of legal experts on its essence and the problems that arise in relation to its application. Methodologically, it is a documentary investigation close to legal hermeneutics. By way of conclusion, the results contain various provisions that clarify the place of this legal and procedural mechanism for exemption from criminal liability, among other mechanisms used for the same purpose. The authors make several notable proposals to improve the regulatory framework of the mechanism under study, which eliminates several identified problems associated with its use.